Synthesis, crystal structures and spectroscopic investigation of new Cu/Schiff-base complexes - Toumi, Ahmed; Rzaigui, Mohamed; Jannet, Hichem Ben (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Three novel Copper complexes, [Cu(L1)2][CuCl2] (1),Â [Cu(L2)Cl] (2) and [Cu2(L3)3Cl2] (3), have been prepared by reaction of CuCl with the Schiff-base ligands L1: N,Nâ€™-bis(thiophen-2-ylmethylene)-ethane-1,2-diamine, L2: N,Nâ€™-bis(1H-pyrrol-2-ylmethylene)ethane-1,2-diamine and L3: N,Nâ€™-bis(2-nitrobenzylidene)-ethane-1,2-diamine in acetonitrile. The solid-state structures of these complexes were determined by X-ray diffraction from single crystal data and characterized by 1H and 13C NMR, IR and UV/Vis spectroscopies. This study shows that (1) is an ionic complex with a Cu(I)-centered cation and an isolated linear dichlorocuprate(I) anion, (3) is a dinuclear neutral complex of Cu(I) while (2)Â is a mononuclear neutral complex of Cu(II). In the three complexes, Cu is tetracordinated in different geometrical environments. The atomic arrangements and spectroscopic properties of the three complexes are reported. Complexes 1-3 exhibit, in the solid state at room temperature, photoluminescence between 320 and 550 nm.